2000
DOI: 10.1097/00002060-200001000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Myofascial Pain

Abstract: Patients with myofascial pain syndrome had higher scores for anxiety than for depression. When combined with neck stretching exercises, ultrasound treatment and trigger point injections were found to be equally effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
77
0
4

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(84 citation statements)
references
References 17 publications
3
77
0
4
Order By: Relevance
“…The superiority of local injection or dry needling for the inactivation of MTrPs is controversial, [2][3][4][5][6][7][8] and hollow needles were used for dry needling in these studies. 2;6 Gunn suggests that the 'hollow needle' induces more tissue injury and is more painful than a 'pointed-tip needle '.…”
mentioning
confidence: 99%
“…The superiority of local injection or dry needling for the inactivation of MTrPs is controversial, [2][3][4][5][6][7][8] and hollow needles were used for dry needling in these studies. 2;6 Gunn suggests that the 'hollow needle' induces more tissue injury and is more painful than a 'pointed-tip needle '.…”
mentioning
confidence: 99%
“…The efficacy of TrP injection in terms of improvement in pain and depression has been well established in the literature [20][21][22]. Ay et al [20] compared the efficacy of TrP injection with lidocaine and dry needling on the pain and depression outcome.…”
Section: Discussionmentioning
confidence: 99%
“…But there is still dilemma present as to whether chronic pain causes depression or depression causes pain [14]. Esenyel et al [15] reported that depression showed improvement by the treatment of MPS. Various trials have been done to evaluate the improvement in pain and depression with trigger point injection therapy with local anesthetic as well as dry needling.…”
Section: Discussionmentioning
confidence: 99%